2010
DOI: 10.1007/s00464-010-1471-6
|View full text |Cite
|
Sign up to set email alerts
|

Emergency preoperative stenting versus surgery for acute left-sided malignant colonic obstruction: a multicenter randomized controlled trial

Abstract: This randomized trial failed to demonstrate that emergency preoperative SEMS for patients presenting with acute left-sided malignant colonic obstruction could significantly decrease the need for stoma placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
207
4
18

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(241 citation statements)
references
References 20 publications
5
207
4
18
Order By: Relevance
“…Such stoma-avoidance advantage of stenting in comparison to emergency surgery ( 33,34 ) has been widely demonstrated with the exception of a study by Pirlet et al . ( 35 ) in which there was no statistically signifi cant diff erence in stoma rate between patients who received a SEMS (43%) and those who did not (57%) prior to surgery. However, all stomas from the SEMS arm were done in technical-failure patients who actually underwent emergency surgery, whereas the majority of successfully stented patients had the benefi t of elective colonic resection and primary anastomosis with an uneventful postoperative course.…”
Section: Discussionmentioning
confidence: 90%
“…Such stoma-avoidance advantage of stenting in comparison to emergency surgery ( 33,34 ) has been widely demonstrated with the exception of a study by Pirlet et al . ( 35 ) in which there was no statistically signifi cant diff erence in stoma rate between patients who received a SEMS (43%) and those who did not (57%) prior to surgery. However, all stomas from the SEMS arm were done in technical-failure patients who actually underwent emergency surgery, whereas the majority of successfully stented patients had the benefi t of elective colonic resection and primary anastomosis with an uneventful postoperative course.…”
Section: Discussionmentioning
confidence: 90%
“…There was no difference between SEMS arm and emergent surgery in primary anastomosis, permanent stoma, in-hospital mortality, anastomotic leak, 30-day reoperation and surgical-site infection rates [82][83][84][85].…”
Section: Colonic Stent Placementmentioning
confidence: 86%
“…15 This guideline is based on the evidence from eight systematic reviews with meta-analysis comparing preoperative stenting with emergency resection for left-sided colonic malignant obstruction, 11,[36][37][38][39][40][41][42] with assimilated data from up to seven RCTs. [43][44][45][46][47][48][49] Three of those RCTs were closed early due to adverse outcomes in the SEMS group (higher 30-day morbidity related to stent perforation), 43,44 or high anastomotic leak rate in the emergency surgery group. 48 The most recently published meta-analysis found that SEMS as a bridge to surgery (n = 195) compared to emergency surgery (n = 187) had a lower overall morbidity (33.1% vs 53.9%, P = 0.03), a higher successful primary anastomosis rate (67.2% vs 55.1%, P < 0.01), and a lower permanent stoma rate (9% vs 27.4%, P < 0.01); however, there was no statistical difference in post-operative mortality (10.7% vs 12.4%).…”
Section: Sems As a Bridge To Elective Surgerymentioning
confidence: 99%
“…13 Manipulation of the tumour by the shearing forces of endoscopy and colonic insufflation is thought to disseminate tumour cells locally and into the circulation. 43 Three RCTs have investigated long-term oncological outcome, all the sample sizes were small (15-26 patients in the SEMS groups), and found increased disease recurrence in the SEMS groups.…”
Section: Sems As a Bridge To Elective Surgerymentioning
confidence: 99%